1999
DOI: 10.1053/joca.1998.0209
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induced by nitric oxide is associated with nuclear p53 protein expression in cultured osteoarthritic synoviocytes

Abstract: This study demonstrates the potential role of NO for the induction of synoviocyte apoptosis in OA. The increased expression of p53 in the nucleus may play a protective role in the control of apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…In fact, an increase of NO, tumour necrosis factor , interleukin 1, metalloproteases (MMP) and reactive oxygen radicals (ROS) is observed in OA, demonstrating the participation of these factors to the genesis and maintainance of degenerative processes in OA (Osborn et al, 1989;Moskowitz, 1993;Lotz et al, 1995;Blanco et al, 2000). NO is mainly produced by chondrocyte, induces apoptosis of the chondrocyte itself (Attisano et al, 1994;Borderie et al, 1999;Fukui et al, 2001;Purple et al, 2001), and inhibits the synthesis of components of cartilage matrix such as collagen type II and GAGs; NO, moreover, increases the activity of MMP, decreases the proliferative response to the Insulin-like Growth Factor-1 (IGF-1) and reduces the endogenous production of Transforming Growth Factor (TGF ), by chondrocyte, furtherly decreasing the synthesis of GAGs and of collagen fibers. Recent in vitro studies (Blanco et al, 2000) have demonstrated that CS blocks the synthesis of NO at the articular level.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an increase of NO, tumour necrosis factor , interleukin 1, metalloproteases (MMP) and reactive oxygen radicals (ROS) is observed in OA, demonstrating the participation of these factors to the genesis and maintainance of degenerative processes in OA (Osborn et al, 1989;Moskowitz, 1993;Lotz et al, 1995;Blanco et al, 2000). NO is mainly produced by chondrocyte, induces apoptosis of the chondrocyte itself (Attisano et al, 1994;Borderie et al, 1999;Fukui et al, 2001;Purple et al, 2001), and inhibits the synthesis of components of cartilage matrix such as collagen type II and GAGs; NO, moreover, increases the activity of MMP, decreases the proliferative response to the Insulin-like Growth Factor-1 (IGF-1) and reduces the endogenous production of Transforming Growth Factor (TGF ), by chondrocyte, furtherly decreasing the synthesis of GAGs and of collagen fibers. Recent in vitro studies (Blanco et al, 2000) have demonstrated that CS blocks the synthesis of NO at the articular level.…”
Section: Discussionmentioning
confidence: 99%
“…44 Furthermore, the appearance of p53 and iNOS in apoptotic macrophages is established in human atherosclerotic lesions. 66 Moreover, a positive correlation between NO formation and apoptosis is also implied for articular cartilage samples from humans with osteoarthritis 67,68 or for the occurrence of human lupus nephritis. 69 Generally, it appears that NO is endowed with the capability to initiate apoptosis in cellular systems, co-cultures, and in vivo.…”
Section: Lessons From Disease Statesmentioning
confidence: 99%
“…6A). NO was chosen as a pro-apoptotic agent owing to its overproduction in the RA joint and its ability to induce apoptosis of FLSs in vitro (21,22). Whereas the protective effect of S1P on SNP-mediated FLS apoptosis was not blocked by a pretreatment of the cells with the S1P 2 antagonist JTE-013 and the S1P 3 antagonist CAY10444 (data not shown), the S1P 1 agonist SEW2871 significantly reduced SNP-mediated FLS cell apoptosis in a concentration-dependent manner (Fig.…”
Section: Protective Effect Of S1p On Snp-mediated Fls Apoptosismentioning
confidence: 99%